Integrating AI-Driven Vocabulary Games from Duolingo to Support Basis Writing Instruction in the EFL Classroom - Vaishnavi; Desi Indah Lestari; Azizah Husda; Fachri Yunanda; Wilda Srihastuty Handayani Piliang (ITScience (Information Technology and Science), 2026)
This study examined the efficacy of using the artificial intelligence (AI) program Duolingo in writing teaching for English as a Foreign Language (EFL), with a focus on enhancing students' descriptive text writing skills. The study addressed students' poor writing skills and limited vocabulary, which often made it difficult for them to articulate concepts effectively. This study's primary goal was to investigate how using Duolingo could improve students' writing abilities, their educational experiences, and teachers' opinions of its use. This study used a Classroom Action Research (CAR) design and a mixed methods approach with a qualitative predominance. While qualitative data were collected through teacher interviews and classroom observations, quantitative data were collected through writing assessments (descriptive texts). The study's findings demonstrated that utilising Duolingo greatly enhanced students' performance, especially in vocabulary, sentence structure, and text usage. After using Duolingo to write, students were more motivated, eager, and self-aware, according to a qualitative data, while teachers reported higher classroom involvement and learning efficacy. In conclusion, Duolingo was a useful tool that helped students build their vocabulary and improve their writing skills when it was methodically incorporated into writing instruction. By offering a workable methodology for incorporating AI-based apps into classroom learning, this study contributed to the field of EFL teaching. To further corroborate these findings, future studies should investigate other text genres and employ various research designs.